2005
DOI: 10.1158/0008-5472.can-04-3250
|View full text |Cite
|
Sign up to set email alerts
|

Emodin Down-Regulates Androgen Receptor and Inhibits Prostate Cancer Cell Growth

Abstract: Hormone-refractory relapse is an inevitable and lethal event for advanced prostate cancer patients after hormone deprivation. A growing body of evidence indicates that hormone deprivation may promote this aggressive prostate cancer phenotype. Notably, androgen receptor (AR) not only mediates the effect of androgen on the tumor initiation but also plays the major role in the relapse transition. This provides a strong rationale for searching new effective agents targeting the down-regulation of AR to treat or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
130
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 42 publications
8
130
2
1
Order By: Relevance
“…The result was consistent with that of halogenated furanones on LuxR protein turnover (Manefield et al, 2002) and that of P. aeruginosa on TraR degradation (Zeng et al, 2008). It has also been reported that emodin can inhibit androgen receptor (AR) transcriptional activity, resulting in AR degradation through a proteasome-mediated pathway and suppressing prostate cancer cell growth in vitro (Cha et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The result was consistent with that of halogenated furanones on LuxR protein turnover (Manefield et al, 2002) and that of P. aeruginosa on TraR degradation (Zeng et al, 2008). It has also been reported that emodin can inhibit androgen receptor (AR) transcriptional activity, resulting in AR degradation through a proteasome-mediated pathway and suppressing prostate cancer cell growth in vitro (Cha et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…It also promotes the apoptosis of human breast cancer BCap-37 cells . Some studies have also reported the effect of emodin on cell death in human prostate, lung, liver, cervical and blood cancer cells (Cha et al, 2005;Su et al, 2005;Jing et al, 2006;Fu et al, 2007;Muto et al, 2007). In this study, compound 5 (emodin) and ampicillin acted jointly against P. aeruginosa more effectively than either of them did alone, suggesting that compound 5 enhanced the activity of ampicillin against P. aeruginosa.…”
Section: Discussionsupporting
confidence: 56%
“…Emodin has long been studied for anti-inflammatory, antibacterial, diuretic, immunosuppressive, and chemopreventive effects. The anticancer effect of emodin is found to be mediated via induction of apoptosis, inhibition of cancer cell growth, antiproliferation, and antiadhesion [22,39,40]. Recently, we have found that emodin can facilitate cytotoxicity in gallbladder carcinoma in the ROS-dependent manner [21].…”
Section: Discussionmentioning
confidence: 99%
“…SP and non-SP cells were harvested, washed, and resuspended in serumfree optimum medium and then injected subcutaneously into 6-week-old BALB/c-nu/nu mice (n = 6 mice per group, purchased from Shanghai Experimental Animal Center). Tumor size was measured every 2 days with a caliper, and tumor volumes were calculated using the formula [22]: p/ 6 · a · b 2 , where a and b were the long and short diameters, respectively. When tumor size of respective cell transplantation model was *100 mm 3 , mice were sorted into 4 equal groups.…”
Section: In Vivo Tumorigenicity and Treatmentmentioning
confidence: 99%
“…42 Therapeutic approaches facilitating AR degradation by the ubiquitin-proteasome pathway may open new avenues in CaP medicine. 43 Although, not fully understood, blockade of the proteasome pathway by hyperthermia or specific blockers may also have future therapeutic values. 44 Reducing AR protein levels in CaP may become a powerful strategy in CaP treatment.…”
Section: Proteasomal Degradation Of Androgen Receptormentioning
confidence: 99%